PATİENT PRİVACY İN EXAMİNATİON AND İNTERVENTİON: A SYSTEMATİC REVİEW - Muslu, Ayşegül (PROFESSIONAL STUDIES: Theory And Practice, 2024)
The aim of this study is to conduct a systematic review of the studies on ensuring body privacy during patient examination or intervention. In the systematic review, 1821 studies conducted between 2015 and 2023 within the scope of patient examination and intervention and by entering the keywords 'Patient privacy, Privacy, Private Life, Patient privacy' in the electronic databases of National Academic Network and Information Center, Higher Education Institution Theses, Pubmed, Google Scholar were scanned. A total of 6 studies that met the inclusion criteria were reached and compared in terms of their results. It was stated that the inpatients thought that their privacy was taken care of by the staff of the institution, the patients who participated in the research observed that the care shown to their privacy was better in private hospitals than in public hospitals, the average level of privacy knowledge of the patients was 73.9%, the average level of privacy evaluation was 81.6%, and the inpatients thought that their privacy was taken care of by the staff of the institution. It was found that the use of apron during the intervention to the patients increased the patient's sense of protection of privacy. In ensuring patient privacy; patient confidentiality all healthcare personnel who work in different institutions by showing the same attention to treating patients may contribute to the increase of level of privacy. It may be recommended to develop different aprons to protect their body privacy during the procedures applied to patients.